Fodder Grasses of Indian Sanctuaries I - Identification of Grasses, Consumed by Herbivores, in the Mahananda and other Wildlife Sanctuaries of North Bengal - Ghosh, S. B. (Indian Forester, 1994)
A number of grasses have been identified, which are highly preferred and consumed by the herbivorous fauna, in the Mahananda Wildlife Sanctuary and other wildlife reserves of North Bengal. On the contrary, the famous alluvial "Savannah" grasslands of this region have been found declining due to various interwoven factors. However, it has been found that, the larger varieties of grasses such as Agrostis brachiata, Anthistiria gigantea var. arundinacea, Capillipedium assimile, Centotheca lappacea, Cymbopogon pendulens, Ischaemum aristatum sub. Sp. imberbe Hack., Panicum flvescence, Rottboelia exaltata, Saccharum arundinaceum var ciliaris, S. bengalensis, S. spontaneum L., Setaria palmifolia etc., which are having underground,enormous, drought resistant rhizomes, are very suitable for plantation purposes and restoration of grasslands. The Savannah of Eastern sub-Himalayas, have been found to be of mixed type of vegetation from ecological point of view and therefore, mixed plantations have been recommended. Alternated patches of tree plantation with Dillenia pentagyna, Eugenia jambolana, Ficus sp. Etc., are advisable. A copious growth of dicotyledonous weeds have been detected which should be eradicated to protect these invaluable Savannah grasslands.